FACTORS PREDICTIVE OF ALCOHOL CONSUMPTION AMONG ELDERLY PEOPLE IN A RURAL COMMUNITY: A CASE STUDY IN PHAYAO PROVINCE THAILAND - Hongthong, Donnapa; Somrongthong, Ratana; Wongchaiya, Pimpimon; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2016)
Background: Alcohol consumption is recognized as a public health issue. Study objectives were to identify factors predictive of alcohol consumption among elderly people in Phayao province Thailand, where there was high prevalence of alcohol consumption. Methods: This was a cross-sectional study. Four hundred elderly people participated in a survey. Data was collected by face-to-face interviews. Chi-square and multivariate logistic regression were used to determine the factors predictive of alcohol consumption among the study subjects. Results: One thirds of elderly (31.7%) had consumed alcohol in their lifetime, and (15.7%) of them were current drinkers. Following univariate analysis, seven factors included gender, working, sickness, smoking, quality of life (QOL), daily activities and economic recession were identified as being significantly associated with drinking (p<0.05). Multivariate analysis revealed four factors to be predictive of alcohol among elderly people: gender (OR=6.02, 95% CI=3.58-10.13), smoking (OR=4.34, 95% CI=2.57-7.34), economic recession (OR=2.79, 95%, CI=1.66-4.71), and QOL (OR=1.86, 95%, CI=1.09-3.16). Conclusion: Gender (male) and smoking were strongly predictive factors of elderly alcohol consumption. Hence, an effort to reduce alcohol consumption should be placed on male elderly and those who smoke. Keywords: Predictive factors, alcohol consumption, elderly people